2017
DOI: 10.1007/s00125-017-4380-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of gestational diabetes in obese women during pregnancy

Abstract: Aims/hypothesis Antenatal obesity and associated gestational diabetes (GDM) are increasing worldwide. While pre-existing insulin resistance is implicated in GDM in obese women, the responsible metabolic pathways remain poorly described. Our aim was to compare metabolic profiles in blood of obese pregnant women with and without GDM 10 weeks prior to and at the time of diagnosis by OGTT. Methods We investigated 646 women, of whom 198 developed GDM, in this prospective cohort study, a secondary analysis of UK Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
120
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 48 publications
13
120
1
Order By: Relevance
“…Other studies have also reported that women with early GDM by WHO 2013 criteria have phenotypic characteristics in common with the metabolic syndrome (24). The UPBEAT study demonstrated that differences in metabolic profile, including exaggerated dyslipidemia, were present at least 10 weeks prior to a diagnosis of GDM in the late second trimester (25). This information may help with identifying women at risk.…”
Section: Discussionmentioning
confidence: 79%
“…Other studies have also reported that women with early GDM by WHO 2013 criteria have phenotypic characteristics in common with the metabolic syndrome (24). The UPBEAT study demonstrated that differences in metabolic profile, including exaggerated dyslipidemia, were present at least 10 weeks prior to a diagnosis of GDM in the late second trimester (25). This information may help with identifying women at risk.…”
Section: Discussionmentioning
confidence: 79%
“…Analytes measured using conventional laboratory platforms (S1 Table) included glucose homeostasis markers, sex hormone binding globulin (SHBG), gamma glutamyl transferase (gGT) and adiponectin. For the purposes of this study and to restrict multiple comparisons, only those analytes identified previously as different between women with GDM and women without GDM at the time of diagnosis (time point 2) [7] were explored. A total of 89 analytes, 83 from the NMR metabolome, were evaluated.…”
Section: Metabolic Profilingmentioning
confidence: 99%
“…We have previously shown that obese women with GDM have differing metabolic profiles from obese women without GDM and that this is evident prior to diagnosis [7]. Using the same dataset, we have hypothesised that the measured analytes might further distinguish between groups necessitating diverse treatment approaches to achieve glucose control.…”
Section: Introductionmentioning
confidence: 97%
“…One of the most common reproductive disorders in women of childbearing age, and the leading cause of infertility, is polycystic ovarian syndrome (PCOS), which can be impaired or even caused by visceral obesity [10]. Maternal health has been reported to worsen as a result of obesity or abnormal weight gain during pregnancy [11][12][13]. Obesity is related to early loss of pregnancy, higher rates of caesarean (c-) section and high-risk obstetrical conditions, in addition to higher maternal and neonatal mortality rates and congenital malformations [8,[14][15][16].…”
Section: Obesity Is Related To Major Health Issues In Womenmentioning
confidence: 99%